2020
DOI: 10.1530/ec-20-0163
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism as first manifestation in multiple endocrine neoplasia type 2A: an international multicenter study

Abstract: Objective Multiple endocrine neoplasia type 2A (MEN 2A) is a rare syndrome caused by RET germline mutations and has been associated with primary hyperparathyroidism (PHPT) in up to 30% of cases. Recommendations on RET screening in patients with apparently sporadic PHPT are unclear. We aimed to estimate the prevalence of cases presenting with PHPT as first manifestation among MEN 2A index cases and to characterize the former cases. Design and methods An international retrospective multicenter study of 1085 ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 70 publications
0
10
0
4
Order By: Relevance
“…Four carried the RET p.Cys611Tyr variant and were 2–3 years old at the last follow-up and therefore below the recommended age for PHPT screening in the ATA-MOD group, starting at age 16 years [ 47 ]. Combined with the fact that the hitherto youngest p.Cys611Tyr carrier reported with PHPT was 40 years at diagnosis, one might methodologically justify including the four cases in our overall cohort as not having PHPT [ 48 ]. This would not change the PHPT frequency but reduce the number of missings to 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Four carried the RET p.Cys611Tyr variant and were 2–3 years old at the last follow-up and therefore below the recommended age for PHPT screening in the ATA-MOD group, starting at age 16 years [ 47 ]. Combined with the fact that the hitherto youngest p.Cys611Tyr carrier reported with PHPT was 40 years at diagnosis, one might methodologically justify including the four cases in our overall cohort as not having PHPT [ 48 ]. This would not change the PHPT frequency but reduce the number of missings to 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Inherited MTC syndromes include multiple endocrine neoplasia type 2 (MEN2A and MEN2B) and familial MTC (FMTC) [8,9]. MTC is associated with pheocromocytoma (PCC) and parathyroid hyperplasia/primary hyperparathyroidism (PHPT) in MEN2A, [10,11], and with PCC, marfanoid habitus and ganglioneuromatosis of the gut and oral mucosa in MEN2B [12]; conversely, FMTC is characterized by multiple cases of MTC in the family, with no other clinical manifestations [13].…”
Section: Introductionmentioning
confidence: 99%
“…3) Recent an international multicenter study reported that the prevalence of PHPT as first manifestation of MEN 2A was only 0.9% (10 cases out of 1085 MEN 2A). 4) In this case, we diagnosed PHPT firstly because of incidental finding of hypercalcemia and then we could confirm medullary thyroid carcinoma during localization study of PHPT. Coexisting thyroid tumor is easily found because parathyroid and thyroid are in adjacent location.…”
Section: Discussionmentioning
confidence: 85%